Analisis Nilai Waktu Uang (Time Value of Money) dalam Perspektif Keuangan Syariah Menggunakan Pendekatan Matematika Ekonomi - anik ismadiana diana; Dessy Boegiyati (Tasharruf : Journal of Islamic Economics and Business, 2024)
Time value of money is a key idea in economic mathematics. It helps analyze money value over time. Today, time value of money is used in investment, financing, and financial decisions. But Islamic finance must adjust time value of money to fit sharia rules that ban interest. This study looks at time value of money in Islamic finance with an economic mathematics approach. The study uses a descriptive qualitative method and a literature study approach. The researcher reviews journals, books, and scientific sources that discuss economic mathematics and Islamic finance. The results show that the time value of money concept can still be used in Islamic financial systems, provided the concept does not contain usury, gharar, or maisir. The application of present value and future value concepts in Islamic financing serves as an economic analysis tool. The tool helps determine financing values in a fair and transparent way. So economic mathematics plays a big role in helping efficient Islamic financial management follow Islamic principles.